Causes and Effects of the Economic Crisis in the Federal Republic of Germany in 1957–1958 - Klimiuk, Zbigniew (Historia i Polityka, 2023)
The economic crisis of 1957–1958 brought to an end the first and started the second post-war business cycle in the West Germany’s economy. The long-term growth trend of the 1958–1970 period was interlaced with two downturns in the economic development, in the 1962–1963 and 1965–1967 periods, respectively. As in the entire period following the World War II, the downturn in economic activity did not lead to an absolute decline in industrial production and gross domestic product (GDP) on the year to year basis, but only to a reduction in the economic growth rate, or in other words – negative deviation of the growth rate from the long-term development trend.